Blockchain dan revolusi transparansi digital: Peran blockchain dalam keamanan data dan transaksi - Sa'diyah, Halimatus (Maliki Interdisciplinary Journal, 2025)
Blockchain is a technology that offers much-needed transparency and data security in the digital era. This technology relies on cryptography to ensure that data within the network is difficult to manipulate and secure from unauthorized access. Each block in the blockchain has a unique digital signature (hash) that makes data immutable without detection by the network. This validation process is supported by consensus mechanisms, such as Proof of Work and Proof of Stake, which maintain the integrity of each new block added to the chain. Through a decentralized system that enables all network participants to access the same data, blockchain prevents a single point of failure, making it highly reliable for sectors that require high trust. This advantage in security and transparency makes blockchain highly relevant for sectors like finance, supply chain, and taxation systems, which demand data integrity that cannot be tampered with.